2015
DOI: 10.1371/journal.pone.0128591
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Transcriptome Responses in Mice (Mus musculus) Exposed to the Nafion Membrane and Its Combustion Products

Abstract: Nafion 117 membrane (N117), an important polymer electrolyte membrane (PEM), has been widely used for numerous chemical technologies. Despite its increasing production and use, the toxicity data for N117 and its combustion products remain lacking. Toxicity studies are necessary to avoid problems related to waste disposal in landfills and incineration that may arise. In this study, we investigated the histopathological alterations, oxidative stress biomarker responses, and transcriptome profiles in the liver of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…55 Over 50% of studies received ratings of medium or high confidence overall (30 out of 53). The exception was Feng et al., 56 in which the Nafion was administered as Nafion membrane. Nafion membranes are composed of and release fluoride, and the study’s internal fluoride measurements indicated that the Nafion was not absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…55 Over 50% of studies received ratings of medium or high confidence overall (30 out of 53). The exception was Feng et al., 56 in which the Nafion was administered as Nafion membrane. Nafion membranes are composed of and release fluoride, and the study’s internal fluoride measurements indicated that the Nafion was not absorbed.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al [115] described the Nafion 117 membrane (N117), a polymer electrolyte membrane (PEM) utilized for different chemical technologies. They carried out studies on the histopathological alterations, oxidative stress biomarker responses, and transcriptome profiles in the liver of male mice exposed to N117 and its combustion products for 24 days.…”
Section: Bindersmentioning
confidence: 99%